The Influence of Work Life Balance, Organizational Culture, and Emotional Intelligence on Employee Performance with Job Satisfaction as Intervening Variable at PT. Pos Indonesia (Persero) Pematang Siantar - Lisa Gresti Sella Damanik; Paham Ginting; Elisabet Siahaan (Budapest International Research and Critics University, 2022)
This study aims to examine the effect of work-life balance, organizational culture, emotional intelligence directly or indirectly through job satisfaction on employee performance at PT Pos (Persero) Pematang Siantar Office. This type of research is descriptive with a quantitative data approach. The population in this study were employees at PT Pos Kantor (Persero) Pematang Siantar, amounting to 51 people and the sample in this study also amounted to 51 people. The data collection method used in this research is by using questionnaires, interviews and observations. The data analysis technique used is path analysis with the help of SPSS. The results of this study found that work-life balance has a significant effect on job satisfaction and employee performance, organizational culture has a significant effect on job satisfaction and employee performance, emotional intelligence has a significant effect on job satisfaction and employee performance. Job satisfaction is able to significantly mediate the effect of work-life balance, organizational culture, emotional intelligence on employee performance.